Observation of two-magnon bound states in the two-leg ladders of (Ca, La)(14)Cu24O41 - Schmidt, Kai Phillip; et al. (Physical Review Letters, 2001)
Phonon-assisted two-magnon absorption is studied in the spin(7)1/2 two-leg ladders of (Ca, La) 14Cu24O41 for E parallel to c (legs) and E parallel to a (rungs). We verify the theoretically predicted existence of two-magnon singlet bound states, which give rise to peaks at approximate to 2140 and 2800 cm(-1). The two-magnon continuum is observed at approximate to 4000 cm(-1). Two different theoretical approaches (Jordan-Wigner fermions and perturbation theory) describe the data very well for J(parallel to) approximate to 1020-1100 cm(-1), J(parallel to)/J(perpendicular to) approximate to 1-1.2. At high energies, the magnetic contribution to sigma(omega) is strikingly similar in the ladders and in the undoped high-T-c cuprates, which emphasizes the importance of strong quantum fluctuations in the latter.